Incidence of Visualization of the Glossopharyngeal Nerve after Pediatric Tonsillectomy. (8th December 2015) - Hill, Courtney A.; Thimmappa, Vikrum; Smith, Mark C.; Chen, Eunice Y.
Abstract : The objective was to determine the incidence of exposure of the lingual branch of the glossopharyngeal nerve during tonsillectomy with a retrospective review of surgical findings in 138 children who underwent total tonsillectomy at a tertiary medical center. Age, sex, surgical indication, tonsil size, congenital abnormalities, operative time, and surgical findings indicating the presence or absence of the glossopharyngeal nerve in the tonsillar fossa were recorded. Statistical analysis was performed with z test, t test, and Fisher's exact test. Thirty‐seven nerves were observed in 28 patients, with preponderance for the left fossa (24 of 37 vs 13 of 37; P =. 01). In a comparison of children with and without exposed nerves, there was no statistically significant difference in mean age (6.89 vs 7.08; P =. 84), proportion of males (14 of 28 vs 54 of 110; P = 1), or proportion of 3 to 4+ tonsils (20 of 28 vs 73 of 110; P =. 66). In approximately 20% of children undergoing tonsillectomy, the lateral pharyngeal musculature incompletely protected the lingual branch of the glossopharyngeal nerve from the tonsil capsule.